Contrasting Narratives of the Israeli-Palestinian Conflict in Polish History Textbooks - Hildebrandt-Wypych, Dobrochna (Frontiers in Education, 2022)
The research critically evaluates ways of narrating the Israeli-Palestinian conflict in Polish secondary school history textbooks. Based on a repeated critical reading and discourse analysis of both Israeli and Arab-Palestinian narratives, the study focuses on the choice of pro-Palestinian and pro-Israeli designations when naming the conflict and the incorporation or silencing of pro-Israeli and/or pro-Palestinian voices in textbook narratives. Reducing Palestinians to a displaced population and depicting Palestinian liberation movement as terrorism are some elements of the an-ti-Palestinian/pro-Israeli textbook narrative. Reducing Israel to the status of a Zionist State and presenting Zionism as a colonial movement are the examples of pro-Palestinian textbook narrative. The research found that although the over simplistic ‘aggressor-victim’ format is not dominant, the coverage of Israeli-Palestinian conflict in most of the analyzed textbooks is unbalanced, sometimes even misleading and implying asymmetrical relations between Jews/Zionists and Ar-abs/Palestinians.